2022
DOI: 10.1038/s41467-022-30445-x
|View full text |Cite
|
Sign up to set email alerts
|

Computer modeling reveals modalities to actuate mutable, active matter

Abstract: Catalytic reactions on flexible sheets generate fluid flows that transform the shape of the sheet, which in turn modifies the flow. These complex interactions make computer models vital for designing and harnessing these feedback loops to create soft active matter that autonomously performs self-sustained mechanical work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Notably, previous theoretical studies suggest that enzyme pumps are powerful enough to impart motility to macroscale sheets. For example, Laskar et al [12,13] predicted that in the presence of the substrate, hydrogen peroxide, catalase-coated millimeter-scale sheets move and change shape spontaneously. Further simulations [14] revealed that asymmetrically enzyme-coated objects can operate as mobile self-propelling pumps.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, previous theoretical studies suggest that enzyme pumps are powerful enough to impart motility to macroscale sheets. For example, Laskar et al [12,13] predicted that in the presence of the substrate, hydrogen peroxide, catalase-coated millimeter-scale sheets move and change shape spontaneously. Further simulations [14] revealed that asymmetrically enzyme-coated objects can operate as mobile self-propelling pumps.…”
Section: Introductionmentioning
confidence: 99%
“…Active colloids are synthetic microparticles that can convert various forms of energy, such as light [ 1 , 2 , 3 , 4 , 5 ], chemical [ 6 , 7 ], magnetic [ 8 , 9 ], electrical [ 10 , 11 ], and acoustic energy [ 12 ] into mechanical motion. Active colloids are found many applications at the microscale, including cargo delivery [ 5 , 13 , 14 ], biosensing [ 15 ], pollution monitoring [ 16 , 17 ], and environmental remediation [ 18 , 19 ], as well as acting as model systems to study the physics of active matter [ 20 , 21 ]. Holding the key to the success of active colloids in both applications and fundamental research is an efficient method to synthesize active colloids of high uniformity in large quantities.…”
Section: Introductionmentioning
confidence: 99%
“…2019; Jiao & Liu 2021), the manufacture of semiconductors (King 1989) and the design of soft and active matter through catalytic reactions (Laskar et al. 2022; Manna et al. 2022) and dynamical wrinkles (Chopin, Dasgupta & Kudrolli 2017; Kodio, Griffiths & Vella 2017; Box et al.…”
Section: Introductionmentioning
confidence: 99%
“…of blood flow (Pedley, Brook & Seymour 1996) and the blood pressure of tall animals (Pedley et al 1996). Moreover, bending deformations of slender objects in viscous or inertial fluids have been manipulated for applications in soft robotics (Kim, Laschi & Trimmer 2013;Matia & Gat 2015;Rothemund et al 2018), the fabrication of microfluidic soft actuators (Thorsen, Maerkl & Quake 2002;Hosoi & Mahadevan 2004;Holmes et al 2013;Fargette, Neukirch & Antkowiak 2014;Gomez, Moulton & Vella 2017;Christov et al 2018;Boyko et al 2019;Jiao & Liu 2021), the manufacture of semiconductors (King 1989) and the design of soft and active matter through catalytic reactions (Laskar et al 2022;Manna et al 2022) and dynamical wrinkles (Chopin, Dasgupta & Kudrolli 2017;Kodio, Griffiths & Vella 2017;Box et al 2019;Pocivavsek et al 2019;O'Kiely et al 2020;Diamant 2021;Guan et al 2022Guan et al , 2023. Despite recent achievements, novel designs of small-scale devices still call for a deeper understanding of elastohydrodynamic couplings.…”
Section: Introductionmentioning
confidence: 99%